A nemzetközi hallgatók vidéki egyetemvárosokra gyakorolt gazdasági szerepe Magyarországon Pécs példáján - Császár, Zsuzsa; Alpek, B. Levente (Közép-Európai Közlemények, 2018)
The aim of the research is to examine the effects of the foreign students of the University of Pécs on the economy of the city and its environment. The number of international students has been increasing in recent years, their presence in the country has an increasing economic role, and their spending on entertainment, relaxation and travel has a positive impact on the local economy and the SME sector. The costs of international students, together with the tuition fees, contribute to the job creation and retention capacity of the region. The base of the research was a complex questionnaire survey of about one year, during which more than 21.8% of the students were involved. Our empirical study reveals the internal structure and magnitude of expenditures. The analysis revealed the main groups and their share of students determined by the spending structure. The results of the study point to the fact that foreign students pose a significant demand on the real estate market and on the apartment market as well as in other areas of the commercial and service sector. The presence of foreign students is a decisive source of revenue, which is likely to continue to grow in the future.